The Influence of the Tandon System on the Productivity of Giant River Prawn (Penaeus monodon Fab.) Cultivation in West Java - Andriani, Yuli; Pratama, Rusky I.; Aisyah, Aisyah (Program Studi Budidaya Perairan Universitas Mataram, 2025)
The reservoir system has become one of the recognized methods for water management in tiger prawn cultivation (Penaeus monodon Fab.) to increase productivity and reduce the risk of disease. Research regarding the application of this system is growing along with the increasing need to maintain optimal water quality in ponds. This review article aims to review various studies that have been carried out regarding the influence of reservoir systems on the productivity of black tiger prawn cultivation in West Java, as well as identifying key factors that influence the success of these systems. Previous studies show that the use of reservoir systems can improve water quality through better circulation, waste filtering, and stabilization of the physical-chemical parameters of pond water. The results of several studies in various shrimp ponds in West Java show a significant increase in productivity, including increased growth rates, shrimp survival, and higher yields. Apart from that, the tank system has also proven effective in reducing the risk of diseases which are often the main obstacle in shrimp cultivation, such as white spot syndrome. However, there are several challenges in implementing reservoir systems, such as high initial investment costs and the need for better technical management. This article concludes that the reservoir system has great potential to be widely adopted in tiger prawn ponds, especially in the West Java area, as long as it is supported by adequate training and technological support. In addition, further research is needed to explore the long-term impacts and development potential of this system in a variety of different environmental conditions.